Development of fuel electrode materials for solid oxide electrolysis cells - Kittiwat, Kamlungsua (Nanyang Technological University, 2022)
Solid oxide electrolysis cells (SOECs) are clean and reliable electrochemical devices that convert water into hydrogen gas to tackle the current and global energy crisis and to prepare for the future energy paradigm shift from hydrocarbon economy to hydrogen economy. The electrode that is responsible for the water reduction reaction (WRR) is the fuel electrode. Several conventional fuel electrode materials that have been used in solid oxide fuel cells (SOFCs) have been employed such as the composite of Ni – YSZ and other perovskite – based materials like SrTi1-xFexO3, Sr2FeMoO6, and PrBaFe2O5+δ. However, the disadvantage of using the composite cermet is poor redox stability and redox cycling due to the formation of the oxide layer on the metallic surface and the agglomeration of metallic particles. Additionally, even though those perovskite – related materials show high stability in reducing and humidified atmospheres at elevated temperatures and competitive electrochemical performances, they can only be used on the fuel electrode side, which limits the extension of the application to symmetric reversible solid oxide electrochemical cells (RSOECs) that can run in both SOFC and SOEC modes. The use of the same materials on both fuel and air electrodes could be cost – effective and more practical. Among a number of perovskite – based materials, Sr2Fe1.5Mo0.5O6-δ (SFMO) has become the most promising candidate as the fuel electrode, as well as the air electrode, for the electrolysis of water in SOECs. Its prominent properties include high redox stability in both oxidizing and reducing environments, high electronic conductivity due to being a p-type nature, and high intrinsic oxygen vacancy for the hydration of water in WRR. Several publications have reported using SFMO as both fuel and air electrode in both SOFCs and SOECs as well. Yet, in order to further improve its electrochemical property, two main strategies have been proposed: doping and forming the composite with electrolyte materials. For the doping strategy, barium (Ba) and potassium (K) are selected to improve the electrochemical property of SFMO. Both Ba and K have larger ionic radii than the substituted strontium (Sr) ion and it could lead to lattice expansion, thereby facilitating oxide migration in the electrode. Moreover, the main difference between Ba and K is their oxidation states. Ba has the oxidation state of +2 but K of +1. The incorporation of K+1 into the crystal structure of SFMO could induce the formation of ionic and electronic defects, which in turn enhance the electrochemical performance. In case of the composite, SDC is chosen to form the composite with SFMO due to its high oxygen capacity and high affinity towards the hydration reaction. Electrochemical studies by DRT analysis under different applied biases and steam contents on Ba0.2Sr1.8Fe1.5Mo0.5O6-δ (B2SFMO) reveal the rate – determining steps for SOFC mode, OCV, and SOEC mode are water desorption, hydrogen adsorption, and charge transfer / water adsorption processes respectively. In addition, polarization resistance behaviour shows that no apparent optimal steam content is observed but it is indicated by the DRT analysis to be 20% steam content. In case of the K – doped SFMO, systematic investigation by TGA and XPS illustrates that K0.15Sr1.85Fe1.5MoO0.5O6-δ (K15SFMO) have a potential to be used as the fuel electrode in SOECs because of its highest oxygen vacancy concentration and highest electronic hole on Fe4+ and Mo6+. Furthermore, rate – determining steps derived from electrochemical studies and DRT analysis for SOFC mode, OCV, and SOEC mode are water desorption, water formation/surface diffusion, and water formation/surface diffusion respectively. Polarization resistance behaviour also suggests that the optimal steam content that is suitable for the application in RSOECs is at 30%. For the SFMO – SDC composites, the amount of 40%wt SDC (SFMO40S) is the most appropriate composition for the composite electrode for SOECs applications due to the highest amount of oxygen vacancy and the highest amount of electronic hole. In relation to that, metal ion incorporation between SFMO and SDC is possibly responsible for the change in the oxygen vacancy and the electronic hole. For electrochemical studies and DRT analysis, respective rate determining steps for SOFC mode, OCV, and SOEC mode are found to be water desorption process, water formation/surface diffusion., and water formation/surface diffusion. In addition, polarization resistance behaviour shows that the optimal steam content for SOFC operation and at OCV is 20%. However, no optimal point is observed in SOEC mode but the decreasing trend in the polarization resistance. Based on the electrochemical studies by DRT and the polarization resistance behaviour, they imply that the composite SFMO40S shows the greatest promise as the fuel electrode for WRR in SOECs and its extensive application as the symmetric RSOEC.